HUBUNGAN SUPERVISI KLINIS DENGAN MOTIVASI KERJA GURU DI MADRASAH ALIYAH NEGERI KOTA BOGOR - Rahmawati, Ima; Lestari, Hana; Soeganda, Bintang Caraka (JURNAL KAJIAN ISLAM MODERN, 2025)
This study aims to determine the relationship between clinical supervision and teachers’ work motivation at Madrasah Aliyah Negeri (MAN) in Bogor City. A quantitative approach was employed using a correlational survey method, with data analyzed through Structural Equation Modeling - Partial Least Squares (SEM-PLS). The sample consisted of 92 permanent teachers selected through purposive sampling. The research instrument was a questionnaire with indicators of clinical supervision covering planning, observation, and feedback, while work motivation indicators included intrinsic, extrinsic, and professional goal motivation. The findings revealed that clinical supervision has a significant effect on teachers' work motivation, with a path coefficient of β = 0.676 and R² = 0.457. Clinical supervision implemented through collaborative and reflective approaches significantly enhances teachers’ sense of professional responsibility, emotional involvement, and enthusiasm for work. These results indicate that improving the quality of clinical supervision is an effective strategy to encourage teachers’ motivation in fulfilling their professional duties. This research contributes to the development of education management practices that emphasize constructive and continuous professional development.